Fertilizantes : calcanhar de Aquíles na sustentabilidade? - Strada, Juliane (2023)
The object of this thesis is the management of the proper handling of fertilizers, since these constitute a key input for ensuring food security. Brazil adopts a model of agricultural commodification, and for that it prioritizes the production of monoculture/monoproduction, which provide greater pressure on environmental goods given the intensive use of the soil. The increase in world demand for food, caused by demographic growth, consolidated the commodity export model, on which Brazilian economic policy is based, as the sector accounts for approximately 1/3 of the Gross Domestic Product (GDP). However, the crisis created, firstly by the COVID-19 pandemic, followed by the conflict in Eastern Europe, exposed the fragility of this model, since Brazil is almost totally dependent on fertilizer imports. So, to maintain the world food supply, it was necessary to introduce more aggressive policies to find alternatives that would overcome the scarcity of the input. Thus, the objective of this thesis is to analyze the relationship between the rational use of fertilizers and the guarantee of food security through sustainable production practices. For this purpose, having as a reference the authors Amartya Sen, Edgar Morin and Ignacy Sachs, based on documentary and bibliographical research through books, scientific articles, official websites, channels and magazines of the agricultural sector, this thesis was elaborated, in which methodological procedure of a theoretical and descriptive nature was used. That said, the guiding hypothesis of this thesis is that with the implementation of appropriate agricultural policies, aimed at the use of alternative sources of fertilizers that can lead to national self-sufficiency, combined with the rational use of the input and with the use of new technologies, achieving there will be less foreign dependency, reduction in the emission of gases into the atmosphere, and reduction of production costs, factors which lead to the achievement of food security, capable of providing greater socio-economicenvironmental equity, with quality of life at short and long term to the population.To obtain the results of this hypothesis, the inductive method was chosen, by which the “[...] approximation of the phenomena generally moves towards ever more comprehensive plans, going from the most particular constructions to the laws and theories (ascending connection)” (MARCONI and LAKATOS, 2022, p. 41). Thus, taking the advent of COVID-19 as a starting point; the conflict in Eastern Europe; the implementation of the National Fertilizer Policy and the use of new technologies, seeking to discover the relationship between them and their impacts to guarantee food security.